Educational Experiences in Informatics: Innovations in Internet Searches in Academic Environments - Argañaras, Pablo E. (2017)
This paper presents innovative experiences in the way of teaching to search information of academic style in Internet to first year students, of the UNRN (Andina headquarters) where Informatics is a transversal topic to their careers. Since 2013 in the Workshop on Informatics a group of teachers inquiries about innovate the way how students make Internet information searches on the academic section, trying that they acquire the ability and the criteria to potentiate their searches, to value their results and to give meaning to the iterative cycle of conformation of correct search keywords, trying this to be useful in the development of their performance as students and later as professionals. We will discuss the methodological recommendations that are offered, the types of tasks and guidelines with which it is tried to innovate the search of information in Internet in academic environments, and the obtained results since 2016.